Packaging design as a marketing tool in promoting Tapai Pulut Sarimah / Nurdalila Meor Sepli - Meor Sepli, Nurdalila (2017)
Packaging design is a vital role to attract consumer, and to persuade them to choose the product and acting as a brand communication. Also, packaging plays a big role in product display as packaging serves an instruments that influences consumer's in their purchasing behaviour. Packaging itself can be stimulates by itself as a self promotion tool for a product. It can be determined by an attractive packaging quality, colour, and others elements of packaging to attract attentions. This is intended to promoting Tapai Pulut Sarimah to international commercialization through new packaging design and advertising, as packaging is one of the promotion tools in advertising. In this paperwork, quantitative method has been used in this research which is 50 respondents in Malacca were interviewed via structured questionaire to gather information regarding their perception to promoting Tapai Pulut Sarimah in international commercialization. The findings of this research is to invented packaging design for international commercialization and identify others elements of packaging design.